Kontribusi Pendidikan Pancasila Terhadap Pembentukan Karakter Religius Siswa Kelas XII SMA Muhammadiyah 2 Singaraja - Estu, Gayuh; Lasmawan, I Wayan (Ganesha Civic Education Journal, 2026)
This study aims to describe the process of instilling religious character values through Pancasila Education in twelfth-grade students of SMA Muhammadiyah 2 Singaraja, to identify the inhibiting factors, and to determine the efforts made to overcome these obstacles. This study uses a descriptive qualitative approach with a case study method. The research subjects consist of the Pancasila Education teacher and twelfth-grade students selected through purposive sampling. Data are collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. Triangulation is applied to ensure the validity of the findings. The results show that the instillation of religious values is carried out interactively and contextually through discussions, case studies, prayer habituation, reflection activities, and teacher role modeling. The values instilled include faith, honesty, tolerance, responsibility, and social awareness. The inhibiting factors include differences in students’ backgrounds, lack of learning interest, limited instructional time, and the influence of the environment and social media. The efforts made include the use of varied teaching methods, strengthening teacher role modeling, continuous character guidance, and collaboration between the school and parents.